Islamic Boarding Schools' Strategy in Implementing the Pancasila Student Profile in Elementary School Students: Strategi Pondok Pesantren Dalam Penerapan Profil Pelajar Pancasila Pada Siswa Sekolah Dasar - Lathifatunnupus, Lathifatunnupus; Fathurrohman, Fathurrohman (Academia Open, 2026)
General Background: Character education remains central to elementary education as schools are expected to develop students’ academic competence, morality, and national values. Specific Background: The Pancasila Student Profile provides a national framework for shaping students who are religious, globally minded, cooperative, independent, critical, and creative, yet its implementation in elementary schools often remains limited by classroom-centered practices. Knowledge Gap: Previous studies have mostly examined the Pancasila Student Profile in general school contexts, while limited attention has been given to Islamic boarding school environments that integrate classroom learning, dormitory life, habituation, and caregiving within a continuous educational system. Aims: This study analyzes Islamic boarding school strategies for instilling Pancasila Student Profile values in elementary school students, examines the synergistic roles of principals, teachers, and caregivers, and identifies supporting and inhibiting factors in implementation. Results: The findings show that character formation is carried out holistically through religious habituation, contextual project-based learning, extracurricular activities, 24-hour dormitory guidance, educator exemplarity, and structured social interaction. The principal, teachers, and caregivers work interdependently through policy design, pedagogical practice, and student life guidance. Supporting factors include a conducive religious environment, continuous habituation, and educator modeling, while inhibiting factors include student background differences, varied understanding, adaptation processes, and limited non-boarding student involvement. Novelty: The study proposes an integrated school dormitory caregiving model, total environment learning, and a dual-factor implementation model. Implications: These findings offer a conceptual contribution to pesantren-based character education and practical guidance for holistic Pancasila Student Profile implementation. Highlights • Character formation is developed through classroom learning, dormitory life, habituation, and caregiving.• Principals, teachers, and caregivers work interdependently in value internalization.• Supporting and inhibiting factors operate through systemic and individual student conditions. Keywords Islamic Boarding School; Pancasila Student Profile; Character Education; Elementary Education; Total Environment Learning